Examination of different C/N ratios, heterotrophic bacteria and plankton abundance on the growth of Nile Tilapia (Oreochromis niloticus) in biofloc system - Gurung, Shailesh; Rai, Sunila; Jha, Dilip Kumar; Mandal, Ram Bhajan; Luitel, Himal (Our Nature, 2025)
Nile Tilapia is a versatile fish renowned for its rapid growth and occurs in a wide variety of freshwater habitats. The trial was done to evaluate the optimum percentage of C:N ratio in biofloc system. A trial was conducted at IAAS, Paklihawa Campus, Bhairahawa, Nepal from 1st March, 2024 to 28st July, 2024 upto 150 days. Altogether 15 circular polytank (500 liter) each were used with stocking density of 40 fish 0.4 m-3 with continuous aeration. Completely Randomized Design (CRD) was set up with 5 treatments, each replicated thrice. The treatments were: (i) T1-without floc (Control) (ii) T2-with floc (C:N-10:1) (iii) T3-with floc (C:N-15:1) (iv) T4-with floc (C:N-20:1) and (v) T5-with floc (C:N-25:1). Molasses was taken as a carbon source. An intitial average weight of mono-sex tilapia fry (4.9±0.8 g) was stocked and 25% CP based pellet feed was given twice daily at 3% of body weight in all the treatments. At initial stage, there was no significant different in Temperature, pH, Ammonia, Nitrite and TSS at p <0.05 in all the treatments. But, there was significance different in Dissolved Oxygen, Floc level and TDS at p <0.05. Similarly, there was no significance different among the treatments in Initial Mean Weight (IMW), Total Initial Weight (TIW) and Initial Number (IN). But there was significantly different among the treatments in final mean weight, final harvest number, final harvest weight, DWG, GFY, NFY, and AFCR among the treatments. The highest final mean weight was found in T5 (58.8±7.6g) and the lowest final mean weight was found in T1 (13.0±0.4g). Result showed final harvest number was found highest in T5 (35.3±1.7) and the lowest in T1 (23.3±0.9). Similarly, the highest final harvest weight was found in T5 (2104.8±68.1g/tank) whereas the lowest final harvest weight was found in T1 (304.4±5.0 g/tank). There was no significantly different among the treatments in the mean value of abundance of bacteria, rotifers and copepda at p <0.05. But there was significantly different among the treatments in the mean value of Cladocera and Protozoa at p <0.05. The study suggests that T5 is found the best option for the growth performance of Nile tilapia in biofloc system.